Minimally invasive preservation versus splenectomy during distal pancreatectomy: a systematic review and meta‐analysis. (16th August 2018) - Nakata, Kohei; Shikata, Satoru; Ohtsuka, Takao; Ukai, Tomohiko; Miyasaka, Yoshihiro; Mori, Yasuhisa; Velasquez, Vittoria Vanessa D. M.; Gotoh, Yoshitaka; Ban, Daisuke; Nakamura, Yoshiharu; Nagakawa, Yuichi; Tanabe, Minoru; et al.
Abstract : Highlight In this systematic review, Nakata and colleagues conducted a meta‐analysis to compare minimally invasive distal pancreatectomy outcomes. Spleen‐preserving distal pancreatectomy had significantly superior outcomes compared with distal pancreatectomy with splenectomy, and when the spleen was preserved, splenic vessel preservation was more effective than Warshaw's technique for reducing splenic complications. Abstract: Background: Minimally invasive distal pancreatectomy (MIDP) has gained in popularity recently. However, there is no consensus on whether to preserve the spleen or not. In this study, we compared MIDP outcomes between spleen‐preserving distal pancreatectomy (SPDP) and distal pancreatectomy with splenectomy (DPS); as well as outcomes between splenic vessel preservation (SVP) and Warshaw's technique (WT). Methods: A systematic search of PubMed (MEDLINE) and Cochrane Library was conducted and the reference lists of review articles were hand‐searched. Results: Fifteen relevant studies with 769 patients were selected for meta‐analyses of DPS and SPDP, while another 15 studies with 841 patients were used for the analysis between SVP and WT. Compared with the DPS group, SPDP patients had significantly lower incidences of infectious complications ( P  = 0.006) and pancreatic fistula ( P  = 0.002), shorter operative time ( P  < 0.001), and less blood loss ( P  = 0.01). Compared with WT, SVP patients had significantly lower incidences of splenic infarction ( P  < 0.001) and secondary splenectomy ( P  = 0.003). Subanalysis for laparoscopic surgery alone had similar results. Conclusions: Based on this study, SPDP has significantly superior outcomes compared to DPS. When a spleen is preserved, SVP has better outcomes over WT for reducing splenic complications.